AGRICULTURAL PRODUCTION AND CONSUMER VULNERABILITY IN SENEGAL AND UGANDA AMID COVID-19 - Michael , K. Nsubuga; Ndiaye , Aissatou D.; Mwesigwa, John R (Research Journal of Agriculture (RJA), 2024)
The Covid-19 pandemic has underscored significant challenges within food security frameworks in Africa, yet comprehensive documentation remains sparse. This article seeks to assess the current state of food systems in sub-Saharan Africa, with a focus on Senegal and Uganda, through the lens of information provided by international institutions and official authorities. The analysis, grounded in reports and articles from these organizations, reveals a complex picture. Agricultural production in both countries has shown resilience against the restrictive measures intended to curb the virus's spread. However, certain sectors, particularly those dealing with perishable goods, have faced substantial obstacles in market access. Most critically, the pandemic has exposed a stark disconnect between agricultural production, food distribution networks, and the precarious condition of consumers. These consumers, both urban and rural, have been severely impacted by the halt in economic activities. This health crisis necessitates a re-evaluation of long-term crisis management strategies, advocating for an integrated approach to food systems that bolsters their resilience and supports the adaptation strategies of all stakeholders involved